Hubungan Penggunaan Game Online dengan Stres Akademik dan Gangguan Tidur pada Remaja di SMKN.1 Motoling Timur - Mamangkey, Amarya Yemima Euyodia; Munayang, Herdy; Usman, Suharno (Program Studi Ilmu Keperawatan Fakultas Kedokteran Universitas Sam Ratulangi, 2025)
Background: Excessive online game use among adolescents can affect both mental and physical health, including causing academic stress and sleep disorders. Objective: This study aimed to examine the relationship between online game use and academic stress and sleep disorders among adolescents at SMK N 1 Motoling Timur. Method: This quantitative study used a cross-sectional design involving 155 tenth- and eleventh-grade students selected through total sampling. Data collection was conducted in June 2025 using three questionnaires: Online Game Playing Frequency, the Educational Stress Scale for Adolescents (ESSA), and the Sleep Disturbances Scale for Children (SDSC). Data were analyzed using Spearman correlation tests. Results: The findings showed that the majority of students had high levels of online game use (48.4%), high academic stress (75.5%), and experienced sleep disorders (91.6%). There was a significant positive relationship between online game use and academic stress (r = 0.346; p = 0.000) and between online game use and sleep disorders (r = 0.493; p = 0.000). Conclusion: The higher the intensity of online game playing, the greater the risk of academic stress and sleep disorders. The study recommends guidance from schools and parents to help adolescents control online gaming habits and manage stress and sleep patterns in a healthy way. Keywords: Online games, academic stress, sleep disorders, adolescents